Strength properties and acid resistance performance of mortar and concrete using blended cockle shell ash and coal bottom ash - Nabilla, Mohamad (2023)
The increasing release of greenhouse gas resulting from activities of the expanding cement industry to cater for the demand of concrete production poses a negative impact to the environment. Harvesting of limestone for cement production causes raw material depletion, environmental destruction, and ecological disruption. Moreover, the disposal of cockle shells from fisheries trade and coal bottom ash from coal power plant significantly pollutes the environment. Successful transformation of the waste materials for concrete product manufacturing would contribute towards reduction in waste disposal and sustainable environment. The present research investigated the potential use of cockle shell ash (CSA) and coal bottom ash (CBA) as partial cement replacement in mortar and concrete. The experimental work was conducted in three stages to achieve each of the three research objectives. During the first stage of the experimental work, various percentages of CSA ranging from 0 to 60% with intervals of 10 were used as partial cement replacement to determine its effect on the setting time of cement paste, flowability and compressive strength of mortar. The optimum CSA content, namely, 10% contributing to strength enhancement of mortar, was used during the second and the third stages. During the second stage, the influence of the different percentages of CBA from 0 to 60% towards setting time of cement paste, flowability and compressive strength was used in 10% CSA blended cement mortar. During the third and thus final stage, the effect of CBA as partial cement replacement on the workability, long-term mechanical performance, water absorption, and acid resistance of cockle shell ash blended cement concrete was investigated. Among the tests conducted were the slump test, compressive strength test, splitting tensile strength test, flexural strength test, modulus of elasticity test, water absorption, and acid resistance. The findings showed that the integration of 10% CSA contributed towards longer setting time and enhanced the compressive strength of mortar. The incorporation of 10% CBA as partial cement replacement in 10% CSA blended cement paste formed lower flowability with increased mortar strength. The use of 10% CBA contributed towards the densification of CSA cement-based concrete through pozzolanic reaction resulting in strength properties enhancement. Upon exposure to acid attack, concrete containing 10% CBA exhibited the lowest mass loss and strength deterioration. The Field emission scanning electron microscopy (FESEM) morphology analysis shows that CSA blended cement concrete containing 10% CBA upon acid attack also exhibits the least degradation. Conclusively, the development of sustainable cement by utilizing local waste from both aquaculture and coal-fired power plants could improve the end product which is mortar and concrete properties by implementing 10% of CSA and 10% of CBA as blended cement. Moreover, the use of CSA and CBA as blended cement also could preserve a green and cleaner environment due to the lesser pollution caused by the cement industry